Analiza struktury przychodów i kosztów powszechnych towarzystw emerytalnych - Chybalski, Filip (Analysis of the Incomes and Costs Structure of Pension Companies, 2008)
The aim of the article is the analysis of the incomes and costs structure of pension companies managing open pension funds in Poland. The author uses taxonomical methods in his research, including distance measures and hierarchical trees. In the conclusion, the author claims that the main of the costs in pension companies are canvassing spends. This can result from the fact that the significant part of the pension companies incomes comes from the contribution fee which is mainly determined by number of open pension fund members. The research confirmed the thesis that pension companies managing bigger pension funds realize higher incomes and costs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 100-111